The difficulty of talent identification: Inconsistency among coaches through skill-based assessment of youth hockey players - Wiseman, A. C.; Bracken, N.; Horton, S.; Weir, P. L. (International Journal of Sports Science and Coaching, 2014)
Talent identification is the process of recognizing participants with the potential to excel in a particular sport. Coaches and scouts are responsible for making an accurate attempt at identifying talent to select athletes for a team roster. The current study used a multi-step approach to assess coaches' perceptions of talent within a local high school. Part 1 consisted of two steps: a) Eight hockey coaches ranked the skills they felt were important when selecting an athlete for a hockey team, b) video clips showcasing the identified skills found in part a) were developed from 13 high school hockey players. In Part 2 seven coaches and two scouts viewed the video clips and generated a list of the top five and bottom five players. Overall, the most frequently identified skills were skating, speed/agility, puck handling, positional play, and shooting. Ranking the players proved challenging with nine of the 13 players being placed in both the top and bottom groups of five. These findings outline the lack of agreement among the coaches/scouts in selecting players which highlights the difficulty in identifying talent. Despite the heterogeneity of the sample of players, even experienced coaches and scouts disagree about what constitutes a skilled hockey player.